RESILIENCE-ORIENTED INTERVENTIONS FOR PATIENTS WITH TRAUMATIC BRAIN INJURY: PROTOTYPES ANALYSIS AND NEW PROGRAM DEVELOPMENT - Assonov, Dmytro (The Ukrainian Scientific Medical Youth Journal, 2021)
Resilience-focused psychotherapeutic interventions can be useful in accelerating the recovery and social reintegration of people with traumatic brain injury (TBI). The number of English-language publications in which authors discuss about resilience-oriented interventions has been growing rapidly in recent years. However, no summarizing of research on resilience-based interventions for people with traumatic brain injury has been made in recent years. The purpose of this study is to analyze and systematize modern resilience-oriented interventions for people with trauma and use them as prototypes to develop our own resilience-oriented program of psychocorrection. Articles for the last 5 years – from January 2016 to February 2021 – were analyzed. The search for scientific literature was conducted using PubMed and APA PsychNET. After analyzing the content and rejection of articles that did not meet the inclusion criteria, the review included 6 original articles, which describe 5 resilience-oriented interventions. The structure and format of the sessions of the analyzed programs are quite variable. The duration of one session varies from 30 to 90 minutes with a frequency of 1 time per week. All analyzed interventions are based on different approaches to understanding resilience and, accordingly, different methods of evaluating results. In addition, most of the analyzed psychocorrection programs focus on many phenomena and possible resilience factors and do not have a single theory or model as a basis. At the same time, a number of models that identify specific components or groups of components and designed to facilitate the selection of therapy targets have been developed in recent years. In further research and interventions, it is promising to focus on key aspects or categories, among which a number of cognitive and emotional components of resilience are distinguished. Currently, there are only the first results of the effectiveness of resilience-oriented interventions in TBI. However, these results allow us to make two important conclusions: 1) by influencing psychological processes, it is potentially possible to achieve a reduction in the intensity of traumatic brain injury symptoms; 2) resilience is a promising target for psychological interventions in traumatic brain injury. After the analysis and systematization of approaches to resilience training, we have developed our own resilience-oriented intervention. The effectiveness of our program will be studied further. Prospects for further research are development and analysis of the effectiveness of interventions aimed at cognitive and emotional components of resilience, adapted to cognitive deficits due to trauma, filled with specific training to develop new skills as well as development of interventions for traumatic brain injury in remote period. As an example of such interventions, we present the program of our own resilience-oriented intervention.